Adaptive Control of Robot Manipulators with Velocity Estimation and Bounded Torque - Aboud, Wajdi Sadik (Al-Nahrain Journal for Engineering Sciences, 2017)
The robot manipulator output feedback problem points out to the controlled system in which the measurements of the joint position are available. In this study, all kinematic and dynamic parameters of robot manipulator are supposed unknown and the manipulator have to follow the desired trajectory. Therefore, the adaptive control problem for robot manipulators based on velocity estimation is investigated. According to the practical robot actuator power limitation, the bounded torque input is also considered in this study. The control algorithm is applied for 2-link manipulator to evaluate controller effectiveness. The design parameters that guaranteed the control performance of closed loop system are chosen by using optimization output constrained method. The proposed controller performances are provided by numerical simulations.